An online social mutual help architecture for multi-tenant mobile Clouds. (1st January 2014) - Ma, Kun; Tang, Zijie
Social mutual help is generally defined as an exchange of verbal and non-verbal messages which convey a plea for help. Recently, more and more people have turned internet to find support and share their experiences. However, the success rate of this online social mutual help is relatively low. Besides, clients are forced to purchase a software to provide services to their users with high cost. Therefore, we aim at improving the success ratio of the help process with a multi-tenant architecture. In this paper, we design an online social mutual help architecture for multi-tenant mobile Clouds. First, we propose a helper recommendation algorithm to accelerate the help process. Second, we present the integration schema of push and pull to propagate the feeds to the potential helpers. Third, we provide some RESTful Web service APIs for the integration with third-party systems. The experimental results show that this architecture improves the success rate and performance successfully and provides the support of data customising of tenants to increase the sparsity.